Different effects of extrusion on the phenolic profiles and antioxidant activity in milled fractions of brown rice. (February 2018) - Zhang, Ruifen; Khan, Sher Ali; Chi, Jianwei; Wei, Zhencheng; Zhang, Yan; Deng, Yuanyuan; Liu, Lei; Zhang, Mingwei
Abstract: Thermal treatment usually causes loss of phenolics while the mechanical effect of extrusion is helpful for releasing bound phenolics from food matrix. Due to the difference in textural property, effects of extrusion on phenolics in different rice fractions were assumed varied. Therefore, differences of the changes of phenolic profiles and antioxidant activities induced by extrusion process in milled fractions of brown rice were explored in this study. Extrusion increased the total phenolics, flavonoids, ferric reducing antioxidant power (FRAP) and oxygen radical absorbance capacity (ORAC) of rice bran by 7.3%, 4.9%, 10.7% and 5.9%, respectively, due to the increases of these parameters in free form. However, extrusion reduced free and bound phenolics, flavonoids, FRAP and ORAC values with a total reduction of 53.7%, 40.1%, 56.5% and 56.1%, respectively, in polished rice and 57.0%, 30.5%, 52.3% and 56.6%, respectively, in brown rice. Seven phenolic acids including ferulic, vanillic, p- coumaric, chlorogenic, gallic, caffeic and syringic acids were detected in rice fractions. Extrusion changed the individual phenolic contents differently among fractions but had no effects on their composition. These findings provide basis for screening resources of functional foods from different milled fractions of brown rice to meet growing demands of functional food market. Highlights: Extrusion had different effects on phenolics and antioxidant activity among milled rice fractions. Extrusion increased the free and total phenolics and antioxidant activity in rice bran. Extrusion decreased phenolic content and antioxidant activity in polished and brown rice. HPLC showed extrusion changed phenolic contents but not composition in rice fractions.